Aggregated Inflation in Poland: Examining Impact of the Energy Commodity Global Prices - Piotr Palac; Justyna Tomala (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego)
The relationship between energy commodity prices and inflation has important implications for fiscal policy and economic stability. The nature of energy commodities is multi‑dimensional, serving both as basic raw materials in production processes and as critical consumer goods. This study focuses on estimating the impact of oil, natural gas and coal prices on inflation in Poland. Through the adoption of multiple regression models using quarterly data from Q2 2000 to Q3 2023, the study aims to estimate the impact of energy commodity prices, particularly oil, coal, and natural gas, on inflation in Poland and to answer the research question: What role do energy commodity prices play in shaping inflation in Poland? The empirical analysis revealed that oil and coal prices significantly influence inflation, reflecting Poland’s energy dependency. Natural gas prices showed a limited impact due to lower consumption and mitigation policy measures. The significant impact of energy prices suggests that energy market developments should be closely monitored for their inflationary potential. The study offers valuable insights for policymakers in their efforts to effectively manage inflationary pressure. The article contributes to the literature by presenting the short‑run relationship between inflation and energy commodity prices, covering long period of time with both financial, COVID‑19 crisis and the Russian aggression in Ukraine.